Parenting styles, psychosocial stimulation, and healthcare access as determinants of social development in children with disabilities - Wilda Rezki Pratiwi; St Hasriani; Asmah Sukarta (Jurnal Ilmiah Kesehatan Sandi Husada, 2026)
Introduction: An estimated 240 million children worldwide live with disabilities, and the World Health Organization reports that they face a substantially higher risk of developmental delay and social exclusion. The Global Burden of Disease study identifies developmental disorders as a major contributor to years lived with disability among children, particularly in low- and middle-income countries where access to inclusive health services remains uneven. In Indonesia, limited integration of psychosocial support within primary healthcare may further compromise social development outcomes. To examine the associations between parenting style, psychosocial stimulation, healthcare access, and social development among children with disabilities. Research Methodology: A quantitative analytical study with a cross-sectional design was conducted among 45 parents or primary caregivers of registered children with disabilities in Sidenreng Rappang Regency, Indonesia. Total sampling was applied. Data were collected using validated structured questionnaires. Associations were analyzed using chi-square tests and multivariate logistic regression, with odds ratios (ORs) and 95% confidence intervals (CIs) reported at α=0.05. Results: Democratic parenting was associated with better social development (OR=4.20; 95% CI:1.01–17.45; p=0.032). Good psychosocial stimulation showed the strongest association (OR=8.00; 95% CI:1.78–35.90; p=0.041) and remained significant after adjustment (AOR=6.75; 95% CI:1.29–35.20; p=0.024). Adequate healthcare access was also associated at the bivariate level (OR=3.33; 95% CI:1.01–10.95; p=0.038). Conclusion: Psychosocial stimulation is the most influential determinant of social development among children with disabilities. Integrating structured caregiver education and family-centered psychosocial support into primary healthcare services is essential to promote developmental equity and reduce long-term social exclusion.